The Importance of Mentorship in Diminishing Workaholism and Increasing Heavy Work Investment: Evidence from the United States - David Sloan; Alan C. Mikkelson; Sebastian Văduva (Amfiteatru Economic)
To examine if mentorship can be utilized to alleviate workaholic tendencies and encourage heavy work investment, our paper explored the links between mentorship functions, mentorship quality, and employee outcomes. Hypotheses were tested among 271 full-time employees living in the United States from various organizations using path analysis. Our research's novelty is the analysis of how mentorship functions of career support, psychosocial support and role modeling have a direct effect on mentorship quality and an indirect effect on employee flourishing, job satisfaction, and job stress. The mentoring function of career support also directly affected the mentorship quality and indirectly affected job stress. A direct effect was found between career support and employee flourishing and job satisfaction. Practical implications, such as the easing of workaholic tendencies and encouragement of heavy work investment, along with limitations, and directions for future research, are analyzed